Good governance based on Maqāsid al-Sharī‛ah in management of tabung masjid: a case study of Malaysia - Zakariyah, Luqman; Sarif, Suhaimi Mhd; Ahmad H.Osman, Rahmah; Abdul Rahman, Shukran (The Islamic Cultural Centre London, 2018)
Malaysia is considered to be one of the most vibrant and creative Muslim countries in the world when it comes to promoting Islamic modernity. Its approach to good governance, especially in Islamic banking and finance, along with its successful administration of Islamic affairs and public welfare in general, is undeniable. However, its attention to good governance and management of Tabung Masjid is still in its infancy. Tabung Masjid in Malaysia continues to lack proper administration and is facing several issues, the most pressing are as follows: inefficient strategic planning for expenditure, accounting, banking, and investing the surplus of Tabung Masjid. This paper examines the ways Tabung Masjid is being managed in Malaysia by focusing on three key aspects, namely, account reporting, banking strategy, and investment of surplus. The paper uses Maqāṣid al-Sharī‛ah approaches to determine whether good governance is adopted in the management of the Tabung Masjid. Four examples have been selected using their regional demographic locations, namely, Selangor, Kelantan, Johor and Saba. The data has been analysed qualitatively, and the results show that while Malaysia has used some of the public funds for the greater benefit of the masses, the potential of Tabung Masjid in the Malaysia has not yet been tapped to achieve the Maqāṣid al-Sharī‛ah of darūriyyāt (Necessities), hājiyyāt (Needs) and tahsīniyyāt (Embellishments).The paper suggests that in order to effectively manage Tabung Masjid, the concept of Maqāṣid al-Sharī‛ah must be fully explored to achieve good governance in managing Muslim public funds.